World Vocational College Skills Competition 2025: Live Ignites Green Light dan Inovasi Promosi EV Tiongkok di Indonesia oleh Politeknik Negeri Sriwijaya - Rahman, M Arief; Peng Jiang; M Lutfi Kurniawan; Nabiel Arinaullah; Ghina Maysya Ayu; Mutiara Syafitri (Yayasan Cendekia Gagayunan Indonesia, 2025)
The rapid growth of electric vehicles (EVs) has encouraged the development of innovative promotion strategies that combine sustainability narratives and digital technology. This community service activity was integrated into the World Vocational College Skills Competition 2025 with the theme “Live Ignites Green Light,” focusing on the promotion of China’s EV products in the Indonesian market through live commerce. The activity involved vocational students from Politeknik Negeri Sriwijaya as the main actors, supported by lecturers and international partners, in designing and implementing live streaming–based promotional content for the Wuling Air EV. A descriptive qualitative approach supported by quantitative performance indicators was applied, including observation, reflective discussions, and analysis of live streaming engagement metrics. The results indicate that the activity enhanced students’ technical skills, communication abilities, leadership, and cross-cultural collaboration competencies. In addition, the live commerce approach contributed to increasing public awareness of eco-friendly mobility and strengthening positive perceptions of EV products. The achievement of a Bronze Medal in the international competition demonstrates the effectiveness of integrating vocational education, digital marketing innovation, and community-oriented engagement. This activity highlights the potential of competition-based community service as a model for developing globally competitive vocational talents and supporting sustainable mobility transitions